Training on an Achievement Data Reporting System for Lecturers and Students at the Faculty of Mathematics and Natural Sciences, Unsulbar - Musafira Musafira; Muh. Rifandi; Fardinah Fardinah (Sarana Ilmu Indonesia (salnesia), 2026)
Documenting and reporting information regarding the achievements of the academic community—particularly students, lecturers, and educational staff—plays a vital role in higher education for institutional accountability and fulfilling accreditation standards. Based on internal data from the Faculty of Mathematics and Natural Sciences (FMIPA) at Unsulbar, there were over 72 total achievements by students and lecturers throughout 2024, yet only approximately 30% were recorded in the faculty's official documents. This significant data gap potentially disadvantages the institution, primarily due to the lack of systematic training and limited proficiency in digital reporting tools among the academic community. The method employed was a needs-based participatory approach, executed in five main phases, including socialization, training, and the implementation of a digital recording system open-access applications. The activity, conducted on August 15, 2025, was attended by 22 representatives of students, lecturers, and staff. The training results demonstrated high enthusiasm from the participants, with 00% of respondents stated that the training was beneficial and greatly assisted the study programs/departments within FMIPA Unsulbar in obtaining data necessary for accreditation purposes. Furthermore, the questionnaire results indicated 100% participant satisfaction with the web application for documenting achievements, and their willingness to use it routinely in the future. This program successfully established an efficient and integrated recording system, representing a critical strategy for fostering a data-driven culture within the institution.